Occupational Hazards Related to Dental Practice and Preventive Measures: An Overview - D. S. Poorya Naik; S. Chetan; B. R. Gopal Krishna; Naveen Shamnur (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
This review highlights the occupational hazards related to the practice of Dentistry. The classification of hazards is based on major sources of risk by system or tissue and by dental office area (dental chair, laboratory, sterilization area, x-ray developing area). Potentially hazardous factors include the general practice setting; specific materials and tools that expose the operator to vision and hearing risks; chemical substances with known allergenic, toxic, or irritating properties; increased microbial counts and silica particles in aerosols produced during tooth preparation and restoration removal; ergonomic considerations that may have an impact on the provider’s musculoskeletal system; and psychological considerations. The identification and elimination of these risk factors should be incorporated into a standard practice management program as an integral part of dental education. Professional organizations can also assist in informing practitioners of potential hazards and methods to deal with them.